Pendidikan Karakter Anak Usia Dini Melalui Cerita Rakyat dan Bermain Singinca’an Pada Suku Melayu Sambas Desa Sepadu - Suratman, Bayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
The focus of this article describes the character education of early childhood in Malay tribalSambas in the village of Sepadu. Through folklore and singinca’an play. Building character in thevillage together is done from early childhood. Character education through folklore andsinginca’an play takes place down and down without coercion and is done actually by theSambas community. Through folklore makes children knoww the culture of Malay Sambas.Besides that, playing singinca’an is also a form of daily activities of early childhoodin the villageof Sepadu in playing singinca’an as well as a form of daily activities of children at an early age inthe village of Sepadu in playing in the home environment. This study was conducteddescriptively based on observations and information sources of researchers obtained frominterview with Sambas Malay tribes in the village of Sepadu